1983
DOI: 10.1159/000163175
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure of Macrophages of the Murine Peyer’s Patch Dome

Abstract: The ultrastructure of macrophages located in the dome of murine Peyer’s patches was examined by transmission electron microscopy. Aggregates of carbon particles as well as numerous other phagocytic and lysosomal inclusions were consistently observed in dome macrophages of carbon-fed mice. Macrophages of both particle-fed and control mice exhibited morphological features of activation. Degenerating macrophages were observed, and evidence is presented that their disintegration involves invasion by other cells. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 11 publications
2
4
0
Order By: Relevance
“…For PLG microspheres Eldridge et al [14,15,21], described the presence of fluorescent parti cles in Peyer's patches for 35 days, results not supported by our work. Our findings rather correlate with those o f Ham mer et al [36] and Jani et al [22] that microspheres are eliminated from Peyer's patches within a few days. As mi crospheres are taken up rapidly and then eliminated within a few days, the most critical parameter is antigen release within this time frame.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…For PLG microspheres Eldridge et al [14,15,21], described the presence of fluorescent parti cles in Peyer's patches for 35 days, results not supported by our work. Our findings rather correlate with those o f Ham mer et al [36] and Jani et al [22] that microspheres are eliminated from Peyer's patches within a few days. As mi crospheres are taken up rapidly and then eliminated within a few days, the most critical parameter is antigen release within this time frame.…”
Section: Discussionsupporting
confidence: 91%
“…bi ological fluids, and thus remains associated to the matrix. In this context, Hammer et al [36] postulated that the major portion o f resorbed particles are transported from the Peyer's patches back into the lumen, and only a small amount of particulate material is translocated into mesen teric lymph nodes and distinct compartments of the system ic immune system. Jani et al [22] described a rapid sizedependent adsorption of microspheres into intestinal Peyer's patches and translocation to other lymphatic com partments within 24 h. In accordance with our findings, they observed a size-dependent decrease in fluorescent beads in Peyer's patches and mesenteric lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…The present observations extend previous reports on the heterogeneity of Peyer's patch macrophages [5,10,21,22], It should be stressed that these heterogeneous macro phages are not distributed randomly, but re side in specific locations. We found that mac rophages near the intestinal lumen showed intense acid phosphatase activity and con tained many large lysosome-like bodies whose sudanophilic lipid material resisted extraction by the solvents used in histological processing.…”
Section: Discussionsupporting
confidence: 91%
“…Considering the weak radiological toxicity of depleted uranium and the low daily quantities of uranium after internal contamination, it seems obvious that possible irradiation effects on the lymphoid follicles present in Peyer's patches were inconceivable for the present study. The question was thus to understand if depleted uranium induced biological modifications of the Peyer's patch function and structure via its chemical toxicity (Leggett, 1989), since a previous study showed modifications of ultrastructural characteristics of macrophages in the Peyer's patch dome with visualization of degenerating macrophages after feeding mice with carbon particles (Hammer et al, 1983).…”
Section: Discussionmentioning
confidence: 99%